2020
DOI: 10.1017/s0967199420000283
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of FSHR, IGF1R, CYP11al and HSD3β in cumulus cells can predict in vitro developmental competence of bovine oocytes

Abstract: Summary The efficiency of in vitro embryo production technologies would be improved by the development of suitable non-invasive biomarkers that allow the selection of good quality cumulus–oocyte complexes (COCs). The present study used whole, single oocyte culture to investigate whether the expression levels of follicle-stimulating hormone receptor (FSHR), insulin-like factor 1 receptor (IGF1R) and three steroidogenesis-related enzymes (CYP11al, CYP19al and HSD3β) in cumulus cells reflected the developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This is also called "oocyte fate" [142]. Although several studies in cattle already found several genes in CCs from germinal vesicle (GV) [16,35,[143][144][145][146][147][148][149][150][151] and MII oocytes [144,152] to be associated with oocyte competence, only a few reports matched the oocyte fate with the transcriptomic profile obtained from the CCs or granulosa cells (Table 2). There is some consensus regarding pathways correlated positively with oocyte competence, including the cell cycle (CCND1, CCNB2, and CCNA2 genes) [143,145,153], cell growth and proliferation, (CD44, TGFB1, EGF, FGF11, PRL, and GH genes) [35,[147][148][149]154], and steroidogenesis (HSD3B2 and CYP11A1 genes) [16,154].…”
Section: Transcriptomic and Proteomic Of Cumulus Cellsmentioning
confidence: 99%
“…This is also called "oocyte fate" [142]. Although several studies in cattle already found several genes in CCs from germinal vesicle (GV) [16,35,[143][144][145][146][147][148][149][150][151] and MII oocytes [144,152] to be associated with oocyte competence, only a few reports matched the oocyte fate with the transcriptomic profile obtained from the CCs or granulosa cells (Table 2). There is some consensus regarding pathways correlated positively with oocyte competence, including the cell cycle (CCND1, CCNB2, and CCNA2 genes) [143,145,153], cell growth and proliferation, (CD44, TGFB1, EGF, FGF11, PRL, and GH genes) [35,[147][148][149]154], and steroidogenesis (HSD3B2 and CYP11A1 genes) [16,154].…”
Section: Transcriptomic and Proteomic Of Cumulus Cellsmentioning
confidence: 99%